2015
DOI: 10.1111/1750-3841.12947
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compositions of Egg Yolks and Egg Quality of Laying Hens Fed Prebiotic, Probiotic, and Synbiotic Diets

Abstract: A 16-wk feeding experiment was conducted to investigate the effects of a prebiotic, isomaltooligosaccharide (IMO), a probiotic, PrimaLac®, and their combination as a synbiotic on the chemical compositions of egg yolks and the egg quality of laying hens. One hundred and sixty 16-wk-old Hisex Brown pullets were randomly assigned to 4 dietary treatments: (i) basal diet (control), (ii) basal diet + 1% IMO (PRE), (iii) basal diet + 0.1% PrimaLac® (PRO), and (iv) basal diet + 1% IMO + 0.1% PrimaLac® (SYN). PRE, PRO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
5
16
3
Order By: Relevance
“…The possible mechanisms by which A. awamori exerts effect are: its superior ability to secrete enzymes able to degrade the non-starch polysaccharides (NSP) and fibre contents of OP, and its role as a probiotic. In addition, the ability to lower egg cholesterol levels had been previously reported for both OP (Hashish and Abd El-Samee, 2005;Saleh et al, 2017) and A. awamori (Imaizumi et al, 1992;Hara et al, 1999;Tang et al, 2015), and this coincides with the increasing demand for low-cholesterol or unsaturated fatty acids in eggs. Therefore, in this study, laying quails were selected as experimental subject to examine the effect of OP with or without A. awamori dietary inclusion on their productive performance, egg quality, and biochemical and antioxidant status.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…The possible mechanisms by which A. awamori exerts effect are: its superior ability to secrete enzymes able to degrade the non-starch polysaccharides (NSP) and fibre contents of OP, and its role as a probiotic. In addition, the ability to lower egg cholesterol levels had been previously reported for both OP (Hashish and Abd El-Samee, 2005;Saleh et al, 2017) and A. awamori (Imaizumi et al, 1992;Hara et al, 1999;Tang et al, 2015), and this coincides with the increasing demand for low-cholesterol or unsaturated fatty acids in eggs. Therefore, in this study, laying quails were selected as experimental subject to examine the effect of OP with or without A. awamori dietary inclusion on their productive performance, egg quality, and biochemical and antioxidant status.…”
Section: Introductionsupporting
confidence: 64%
“…Moreover, Saleh et al (2017) found a significant decrease in the yolk cholesterol in groups fed A. awamori. Other researchers observed also the beneficial effects of probiotic on egg quality such as lower cholesterol content (Mikulski et al, 2012;Tang et al, 2015).…”
Section: Egg Quality Criteriamentioning
confidence: 87%
See 2 more Smart Citations
“…Hen eggs have been consumed by humans for thousands of years because they are nutritionally dense, relatively simple and are accepted in most cultures. Despite the nutritional value, there are some potential health issues arising from high level of cholesterol in the egg yolk (Tang et al., ). It is well known that eggshell quality and egg trait are of major importance to the customer preference.…”
Section: Introductionmentioning
confidence: 99%